1986
DOI: 10.1111/j.1468-2958.1986.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Turning Points in Developing Romantic Relationships

Abstract: The 80 partners from 40 romantic relationships were independently interviewed using the RIT procedure with regard to the turning points of their respective relationships; 26 types of turning points were found, which reduced to 14 supratypes. These supra-types differed in their association with relational commitment, with some events strongly positive, some strongly negative. and others relatively modest in reported change in commitment. About half of the turning points involved explicit metacommunication betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
259
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(260 citation statements)
references
References 30 publications
1
259
0
Order By: Relevance
“…Underwood (2009) theorized that CL is most likely to be beneficial when partners have a shared perspective about their interaction. Yet, relationship partners often disagree about their interactions, even when focusing on relatively concrete behaviors (e.g., Baxter & Bullis, 1986;Thomas & Fletcher, 1997). These differences may reflect motivated cognition-for example, people tend to interpret partners' behavior in a manner that reflects their motives, personality traits, or situationally specific goals (Baldwin, 1992;Murray, 1999).…”
Section: An Interpersonal Perspectivementioning
confidence: 99%
“…Underwood (2009) theorized that CL is most likely to be beneficial when partners have a shared perspective about their interaction. Yet, relationship partners often disagree about their interactions, even when focusing on relatively concrete behaviors (e.g., Baxter & Bullis, 1986;Thomas & Fletcher, 1997). These differences may reflect motivated cognition-for example, people tend to interpret partners' behavior in a manner that reflects their motives, personality traits, or situationally specific goals (Baldwin, 1992;Murray, 1999).…”
Section: An Interpersonal Perspectivementioning
confidence: 99%
“…They have also had interest in particular changes that the turning points bring about, such as levels of commitment, relational satisfaction (e.g., Baxter & Bullis, 1986;Surra, 1987), self-efficacy (i.e., Docan-Morgan, 2011), and closeness (e.g., Golish, 2000;Johnson, Wittenberg, Villagran, Mazur, & Villagran, 2003;Johnson et al, 2004;Poulos, 2012). As noted, nonverbal behavior has not been the primary focus of this scholarship.…”
Section: Nonverbal Cues As Turning Pointsmentioning
confidence: 99%
“…First, previous research only suggests a few behaviors-touch, space, environment, and time-that may trigger relational change. To better assess the types of cues recognized as important to turning points, and consistent with similar arguments made in other contexts (e.g., Docan-Morgan & Manusov, 2009) Second, Baxter and Bullis (1986) Third, given that nonverbal behaviors are both indicators of relationships (Guerrero & Floyd, 2006) and also are made sense of within the larger narrative of a relationship (Manusov & Koenig, 2001), we ask the following: Last, the current study also investigates the reported outcomes of relational turning points. As noted, most research (e.g., Golish, 2000) on relational turning points examines only one outcome variable (i.e., closeness).…”
Section: Nonverbal Cues As Turning Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning point analysis investigates the changing nature of relationships by examining events that contribute to specific changes. Turning points are events that create positive or negative changes in a relationship, and are associated with relational satisfaction, commitment, and metacommunication (Baxter & Bullis, 1986). Examining turning points may lead to a better understanding of which events relate to change in mentoring relationships.…”
Section: Future Directions: a Life Cycle Approach Of Mentoring Relatimentioning
confidence: 99%